PEMANFAATAN ARANG AKTIF DARI KULIT KACANG (Arachis hypogea L) DENGAN AKTIVATOR NaOH DAN H2SO4 UNTUK ADSORBEN ION BESI - Taupan Riski Baruna Aji (FT-USNI, 2022)
Along with the development of technology for utilizing peanut shells, which are usually only used as waste, it can also be used as activated charcoal which is widely used as an adsorbent for gas purification, metal absorbent, oil purification and water purification. Peanut shells (Arachis hypogea L) can also be used as activated charcoal by first removing the water content, ash content and iodine content, then activation using an activator. In this study, the activator used was a solution of NaOH and H2SO4. The purpose of the study was to determine whether peanut shells could be used as activated charcoal as an adsorbent of ion (Fe) levels in domestic waste. From the research that was conducted, peanut shells were used as raw material for making activated charcoal in determining the water content in heating 700 0C, the results were 11.62% and the heating ash content at 700 0C was 6.54%, then charcoal that had been heated heated and soaked using a solution of NaOH and H2SO4, with variations in the concentration of each 10% 20% and 30% solution then the best results obtained from activated charcoal in the H2SO4 activator with a concentration of 30% with the results of an ash content of 2.13% water content of 0.18% and an iodine content of 1055.30 (mg/g), the best activated charcoal in a 30% H2SO4 solution was then tested for ion (Fe) levels in domestic waste by triple testing and from the results in front the average was 91 .11%.